Totalitarianism and Political Religion : an Intellectual History. - Gregor, A. (Stanford University Press, 2012)
The totalitarian systems that arose in the twentieth century presented themselves as secular. Yet, as A. James Gregor argues in this book, they themselves functioned as religions. He presents an intellectual history of the rise of these political religions, tracing a set of ideas that include belief that a certain text contains impeccable truths; notions of infallible, charismatic leadership; and the promise of human redemption through strict obedience, selfless sacrifice, total dedication, and unremitting labor. Gregor provides unique insight into the variants of Marxism, Fascism, and Nationa.